2015
DOI: 10.1175/jpo-d-15-0031.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tidal Oscillatory Salt Transport in a Partially Stratified Estuary

Abstract: Tidal oscillatory salt transport, induced by the correlation between tidal variations in salinity and velocity, is an important term for the subtidal salt balance under the commonly used Eulerian method of salt transport decomposition. In this paper, its mechanisms in a partially stratified estuary are investigated with a numerical model of the Hudson estuary. During neap tides, when the estuary is strongly stratified, the tidal oscillatory salt transport is mainly due to the hydraulic response of the haloclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Here, the tidal advective salt transport represents the residual salt transport caused by the advection of tidal salinity by the tidal velocity, which is called tidal oscillatory salt flux in Lerczak et al (2006) and Wang et al (2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the tidal advective salt transport represents the residual salt transport caused by the advection of tidal salinity by the tidal velocity, which is called tidal oscillatory salt flux in Lerczak et al (2006) and Wang et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…In well-mixed estuaries, for instance, the tidal oscillatory transport due to temporal correlations on the tidal time scale between the longitudinal velocity and salinity can be the predominant salt import mechanism (McCarthy 1993;Wei et al 2016). The tidal oscillatory salt transport can also be significant in partially stratified estuaries such as the Hudson estuary during neap tides (Chen et al 2012;Wang et al 2015). Even in salt wedge estuaries such as the Merrimack River, the landward salt transport is mainly associated with the tidal oscillatory processes rather than with the steady sheared gravitational circulation (Ralston et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2012) and Wang et al (2015) showed that the Eulerian exchange flow exhibited a large, longitudinal variation in the Hudson estuary due to the variation of the tidal dispersion term, whereas TEF provided a smooth, continuous variation. These analyses demonstrated that TEF provides a more robust means of quantifying exchange flow in regions of complex interactions between tidal flow and topography.…”
Section: Introductionmentioning
confidence: 99%
“…This term is sometimes parameterized as a tidal dispersion term using an ad hoc along-channel diffusivity [e.g., Hansen and Rattray 1965; see review by Geyer and MacCready (2014)]. However, the mechanisms contributing to tidal dispersion vary for different estuaries (Okubo 1973;Fischer 1976;Hunkins 1981; Lewis and Lewis 1983;MacCready and Geyer 2010) and even for different cross sections in one estuary (Chen et al 2012;Wang et al 2015). Some studies have shown that when using the Eulerian method, time-varying processes were represented as dispersion when they were more appropriately represented as part of the advective exchange flow (Dronkers and van de Kreeke 1986;Geyer and Nepf 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the tidal distortion of the vertical salinity gradient may be a key process leading to the tidal oscillatory salt flux. Such tidal distortions can be caused by the vertical heaving of a pycnocline, described by Geyer and Nepf (1996) and Wang et al (2015) in the Hudson River, as well as by tidal asymmetries in shear and/or stratification (e.g., J. H. Simpson et al, 1990).…”
Section: Salt Balance In the Passaic Rivermentioning
confidence: 99%